The criminal proceeding for facts of organized crime: from the maxi-processo to the «big process» - Renzo Orlandi (Revista Brasileira de Direito Processual Penal, 2021)
In this article, the transformations in the criminal procedure after the maxi-processo are analyzed, specifically the formation of a special criminal procedure destined to the pursuit of organized crime, the «big process», «diffuse», in which the singular and concrete criminal proceedings come together, with the serious risk of losing his individuality.